Petrographic analysis and diagenetic history of the Viola limestone at Stephen’s Ranch, in the Morrison northeast field of Clark County, Kansas - Linares, Aria (Kansas State University, 2016)
The Viola Limestone is a prominent petroleum reservoir in the Mid-Continent Region, particularly in Oklahoma and Kansas. Coral Coast Petroleum established production from the Viola Ls. in 2011 in their Stephens Ranch lease in Clark County, south-central Kansas. Development of this lease has been hindered by the unpredictable production rates encountered in each of the subsequent eleven development wells. Infield drilling locations to date were chosen by favorable structural position as determined by 3D seismic. The best reservoir conditions, however, do not necessarily coincide with structural position. It was the purpose of this study to determine whether the ideal porosity and permeability are controlled by depositional environment, diagenetic alterations, or a combination of these factors. Several approaches to solve this question were implemented and utilized, including well log analysis, petrographic inspection of well cuttings and thin sections, and the application of the Scanning Electron Microscope (SEM). An exploration model of the Viola Ls. in this field was developed, where the Viola A and B zones were dolomitized during during marine transgressions by mixing of sea water with other Mg-rich fluids. Reservoir conditions are found where these facies were preserved as paleotopographic highs during a subsequent sea level low-stand. These preserved dolomitized facies correspond to the seismic facies identified by seismic attributes in a 3D seismic study by Vohs (2016).
Keywords: carbonate; dolomite; Viola Limestone; diagenesis; Ordovician; hydrocarbon production in Kansas